2015
DOI: 10.1371/journal.pone.0132936
|View full text |Cite
|
Sign up to set email alerts
|

An Update of the Evolving Epidemic of blaKPC Carrying Klebsiella pneumoniae in Sicily, Italy, 2014: Emergence of Multiple Non-ST258 Clones

Abstract: BackgroundIn Italy, Klebsiella pneumoniae carbapenemase producing K. pneumoniae (KPC-Kp) strains are highly endemic and KPC producing CC258 is reported as the widely predominating clone. In Palermo, Italy, previous reports have confirmed this pattern. However, recent preliminary findings suggest that an epidemiological change is likely ongoing towards a polyclonal KPC-Kp spread. Here we present the results of molecular typing of 94 carbapenem non susceptible K. pneumoniae isolates detected during 2014 in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
74
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 25 publications
9
74
0
1
Order By: Relevance
“…bla has been commonly associated with ST101 worldwide and, according to the results of an 11-year (2001 to 2011) molecular epidemiologic study of bla in Europe and North Africa, ST101 is the most frequently observed sequence type (13). Among the carbapenem-resistant K. pneumoniae STs identified in this study, the emergence of colistin resistance had been already reported in KPC-2-producing ST101 (14) and bla KPC-2 -and bla CTX-M -producing ST307 (15,16). Carbapenem-and colistin-resistant isolates of ST437 have been reported previously (17).…”
supporting
confidence: 61%
“…bla has been commonly associated with ST101 worldwide and, according to the results of an 11-year (2001 to 2011) molecular epidemiologic study of bla in Europe and North Africa, ST101 is the most frequently observed sequence type (13). Among the carbapenem-resistant K. pneumoniae STs identified in this study, the emergence of colistin resistance had been already reported in KPC-2-producing ST101 (14) and bla KPC-2 -and bla CTX-M -producing ST307 (15,16). Carbapenem-and colistin-resistant isolates of ST437 have been reported previously (17).…”
supporting
confidence: 61%
“…Further surveillance will be needed to follow this trend. In their study of bla KPC -carrying K. pneumoniae in Palermo, Italy, Bonura et al (16) reported a shift toward a polyclonal epidemic, which highlights that the evolution of resistance is complex and that the importance of changing patterns of resistance should not be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of KPC-producing K. pneumoniae in Palermo, Italy, also confirmed the emergence of ST258 beginning in 2008 (4). More recently, a 6-month surveillance performed in Sicily suggested that a major epidemiological change is likely ongoing in this geographic area, with ST258 still being prevalent but circulating along with several additional STs, including ST307 and ST273 (4).…”
mentioning
confidence: 82%